Student Role Knowledge Well-being Social in Formation Characteristics Independence of Foster Children During the Covid-19 Pandemic in Orphanages Happy Child Care , Medan, North Sumatra - Hartanti, Dinda Maulidia (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
Abstract : The Covid-19 pandemic is a difficult time passed all circles society , including the impact on children foster . Independence is a must applied to children foster during the pandemic This implanted independence so as not to always served by a caretaker in do his task . 1) A lot of effort done student in help independence child foster care during the pandemic ie with method guide child foster For guard cleanliness environment and always activity use a mask too guard distance , 2) A lot of effort done student in help independence with help child foster hone creativity from House as well as always guard cleanliness 3) Lots of effort done student in help independence child foster on aspects habituation clean self . Science Study Program Students Welfare Social that has go through Practice Work Field expected capable apply results counseling to life daily . Keywords : Independence , Practice _ Work Field (PKL), Panti Raising Happy Children